M, media Lift the Flap Book Media and Learning Motivation Improve Reading Literacy Skills in Early Elementary School Grades - Fajria, Lusiana; Utoyo , Setiyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The current problem is that students lack the motivation to learn. This is because students feel bored in participating in learning activities in class. This study aims to analyze the effect of Lift the Flap Book media and learning motivation on children's reading literacy skills in early elementary school classes. This type of research is an experiment using a 2 x 2 factorial design. The sampling technique used in this study is the Simple Random Sampling technique. The research sample is 40 students. The method used in collecting data is a test. The instruments used in collecting data are questionnaires and test questions. The data analysis technique used in this study using SPSS 22 is two-way ANOVA (two-way ANOVA). The results of the study showed that using the Lift the Flap book had a significant effect on children's early literacy skills. The results of the study in the experimental class showed that there was a significant effect between learning motivation and children's early literacy skills. Second, there is an interaction effect between Lift the flap book and learning motivation on children's literacy skills. It is concluded that lift the flap book media and learning motivation on reading literacy skills in early elementary school classes. The implications of this study indicate that the use of interactive and fun media can be an effective approach in improving students' literacy skills in early grades.